An effective formaldehyde gas sensor based on oxygen-rich three-dimensional graphene. (30th April 2022) - Zhang, Shu; Pang, Jinbo; Li, Yufen; Ibarlucea, Bergoi; Liu, Yu; Wang, Ting; Liu, Xiaoyan; Peng, Songang; Gemming, Thomas; Cheng, Qilin; Liu, Hong; Yang, Jiali; et al.
Abstract: Three-dimensional (3D) graphene with a high specific surface area and excellent electrical conductivity holds extraordinary potential for molecular gas sensing. Gas molecules adsorbed onto graphene serve as electron donors, leading to an increase in conductivity. However, several challenges remain for 3D graphene-based gas sensors, such as slow response and long recovery time. Therefore, research interest remains in the promotion of the sensitivity of molecular gas detection. In this study, we fabricate oxygen plasma-treated 3D graphene for the high-performance gas sensing of formaldehyde. We synthesize large-area, high-quality, 3D graphene over Ni foam by chemical vapor deposition and obtain freestanding 3D graphene foam after Ni etching. We compare three types of strategies—non-treatment, oxygen plasma, and etching in HNO3 solution—for the posttreatment of 3D graphene. Eventually, the strategy for oxygen plasma-treated 3D graphene exceeds expectations, which may highlight the general gas sensing based on chemiresistors.